AKIBAT HUKUM BENTUK-BENTUK RESTRUKTURISASI PERUSAHAAN DI INDONESIA - Sagitha Surya, Satrisca; Suyatna, I Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 05, Juli 2014, 2014)
According to Article 1 Letter b Act Number 3 of 1982 on Company Registation Obligatory, company is any form of business that runs any type of business to gain profit, which permanently and continuously established, operating and domiciled in the territory of the Republic of Indonesia. The existence of the numerous company in Indonesia causes high competitiveness between a company and the other company. Restructuritation is a step a company takes to hold it existence. There are 4 (four) kinds of restructuritation, which are merger, consolidation, acquisition and the separation of state-owned. The paper use the normative method from law literatures and statute. The purpose of this writing is to determine the forms of restructuritation and to understand how the legal implications of such restructuring forms, such as assets and liabilities transfer, shareholders transfer and the loss of company legal status.
Keywords: Legal Implications, Restructuration, Company